The EFL Learners’ Lens on Online Teaching Speaking and its Effective Teachers at Islamic Higher Education - Erna Iftanti (Dinamika Ilmu, 2022)
Learning language skills such as speaking, which is emphasized by practicing a lot, should also adjust to the online learning platform. This paper is then intended to portray how EFL learners perceive online learning to learn and improve their speaking skills. The study was done by administering an online questionnaire survey to forty-six students of UIN Sayyid Ali Rahmatullah Tulungagung who attended Speaking for Daily Interaction Subject. This study revealed that Google meet is the most helpful learning application for online speaking classes, but attending offline classroom meetings is preferable to improve their speaking skills. Although there are some challenges, such as feeling insecure, less social contact with practicing speaking, and a bad internet connection, they claim that their skills of using a daily expression in English are getting improved through using appropriate online learning applications taught by an effective teacher. The portrait of the effective teacher of speaking was also ferreted out. These findings are pedagogically implemented to conduct an effective online speaking class. Yet, because this study was conducted with a small scope of respondents, then future researchers are suggested to include a wider scope of respondents in order to contribute to the finding of this research.